Exploring physical literacy, physical activity, motivation, and learning outcomes in elementary school physical education - Adi S; Soenyoto, Tommy; Yuwono, Cahyo; Nurharsono, Tri (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Physical education in elementary school plays an important role in building physical literacy, increasing physical activity, and motivating students to achieve optimal learning outcomes. However, the relationship between these factors has not yet been studied holistically, so a more in-depth study in elementary schools is needed. Methods: This type of research is correlational research using a quantitative approach. The sample of this study was elementary school students in grades IV, V, and VI. The sample is 270 students. This study used purposive sampling for 8-12 years. Sampling in this study used tests and questionnaires for tests conducted on aspects of physical literacy, IPAQ (International Physical Activity Questionnaire), motivation, and observation of student learning outcomes. Data analysis using the SPSS version 25.0 data processing application program with normality, linearity, and correlation tests. Finding/Results: Physical literacy, physical activity and motivation data and learning outcomes are normal. The same thing also happened in the linearity test on the four aspects. Physical literacy to learning outcomes is positively correlated. 0.000 < 0.05. Physical activity to learning outcomes is positively correlated. 0.007 < 0.05. Motivation to learning outcomes is positively correlated. 0.000 < 0.05. Future research can focus on developing and testing intervention programmes that integrate these three variables to improve student learning outcomes holistically. In addition, it is important to conduct studies that explore causal relationships through experimental designs, as well as consider differences in influence across educational levels, from primary to tertiary. Conclusion: Physical literacy, physical activity, and motivation are specific to the learning outcomes of physical education. Understanding and paying attention to the relationship between physical literacy, physical activity, and motivation can help educators design more effective and enjoyable learning experiences in physical education, improving student learning outcomes.